Impact on the quality of life of patients undergoing thyroidectomy: A literature review - Linard Carneiro, Ana Carolina; Josival Pereira de Araújo Junior,; Ankilma do Nascimento Andrade Feitosa, (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2025)
Introduction: The study of thyroid gland alterations, coupled with advances in diagnostic testing, has allowed for greater accessibility in detecting diseases, leading to various indications for thyroid resection. However, these approaches present complications, such as recurrent laryngeal nerve injury. There is also an increase in anxiety and depression scores. Objective: To evaluate current literature data on the impact on the quality of life of patients undergoing thyroidectomy. Methodology: This is an integrative literature review, conducted in February 2024, through the selection of scientific articles published in journals indexed in the SCIELO and PubMed databases using the descriptors "Thyroidectomy" and "Quality of life" separated by the Boolean operator AND. The descriptors were searched in DeCS. Results: Surgical management is the basis of treatment for thyroid neoplasms. Although it reduces local recurrence, it presents twice the risk of recurrent laryngeal nerve and parathyroid injury, leading to a decline in quality of life. Lack of social support, coupled with fear of cancer recurrence, was identified as a factor impacting patients' quality of life. Conclusion: Thus, the need for individualized care is highlighted, with support from professionals addressing the physical, psychological, and social aspects.